Employers’ perspectives on the employability of music graduates in Hefei, China / Xu Zitong - Xu , Zitong (2025)
For all university graduates in today's society, employment represents a significant source of stress and challenge. A range of social and personal factors contribute to this stress. The objective of this study was to examine the perceptions of employers regarding the employability of music graduates in music education institutions in Hefei City. This study sought to address two key research questions: (1) How is the employability of current music graduates perceived by the employers of music education institutions? (2) What recommendations can be made to improve the employability of music graduates from the employers' perspective? Five employers were interviewed to ascertain their perceptions of the employability of music graduates. The interviews were conducted using a semi-structured approach and employed a categorization of employability into specialist skills and comprehensive employability. The present study examined employers' perceptions of the employability of music graduates, focusing on six key areas: professional competence, communication skills, adaptability, work attitude, career planning, and teamwork awareness. Employers were invited to offer their views and provide specific suggestions on how they expected graduates to develop their employability. Furthermore, employers concurred that the underemployment of music graduates is predominantly attributable to the deficiencies inherent in the institution's curriculum and training model. Consequently, employers articulated their discontent with the prevailing levels of employability exhibited by music graduates and underscored the necessity for uninterrupted enhancement to align with the competencies demanded by the role.